Instructional design and engaging pedagogical principle into the building e-learning content - Le Đức Long; Tran Văn Hạo; Hunger, Axel (Journal of Technical Education Science, 2011)
Instructional design has being considered and applied in building e-Learning systems right from the early history of its developing literature. Thank to these applications, the e-Learning systems have combined the design of learning contents with the selection and use of technologies effectively. Recently, instructional design is more interested in e-Learning fields because the needs of developing system which used to serve in the educating and training problem are increasing. It leads to many researches to solve the existed limitations of on-line learning and teaching as well as improve the quality of e-Learning system. The paper presents a general review of instructional design field and the use of the instructional design models for developing e-Learning systems now, especially focusing on the problems that related to building on-line learning content. In each section, the paper discusses the main objects and disadvantages to solving, in which the key point is the need of engaging pedagogical principle into building learning content process. The end of paper also introduces shortly Knowledge Graph, a model proposed by the paper authors. It aimed to engaging pedagogical principle into process of designing and building on-line learning content